2017
DOI: 10.12973/eurasia.2017.00696a
|View full text |Cite
|
Sign up to set email alerts
|

Life Sciences Teachers Negotiating Professional Development Agency in Changing Curriculum Times

Abstract: This article probes teacher responses to three curricular reform initiatives from a South African situated contextual perspective. It focuses on Life Sciences teachers who have initially reported feeling overwhelmed by this rapidly changing curriculum environment: adopting and re-adapting to the many expected shifts. The research question posed is: How do teachers negotiate and reinterpret their professional roles and responsibilities in the continually changing environment? A qualitative research design engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The CAPS LS was first introduced in grade 10 in 2012, and in 2013 and 2014 it was to be introduced at grades 11 and 12 respectively. This means that during the period of 2012 to 2014 LS teachers were involved in teaching two curricula as a result of the overlap period of phasing out one (the National Curriculum Statement (NCS) Further Education and Training Life Sciences for Grades 10-12) and introducing another curriculum (CAPS LS grade 10-12) (Singh-Pillay & Samuel, 2017). The mandatory practical examination is one hour (DoE, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The CAPS LS was first introduced in grade 10 in 2012, and in 2013 and 2014 it was to be introduced at grades 11 and 12 respectively. This means that during the period of 2012 to 2014 LS teachers were involved in teaching two curricula as a result of the overlap period of phasing out one (the National Curriculum Statement (NCS) Further Education and Training Life Sciences for Grades 10-12) and introducing another curriculum (CAPS LS grade 10-12) (Singh-Pillay & Samuel, 2017). The mandatory practical examination is one hour (DoE, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has seen rising interest in teacher agency as a phenomenon impacted by various forces (Priestley et al 2015;Singh-Pillay and Samuel 2017;Tran 2018), with policy implementation as one of the major forces. Priestley et al's (2015) ecological model of teacher agency emphasises the role played by teachers' experiences (past), their material conditions (present) and their aspirations (future).…”
Section: A Posthumanist Reading Of Teacher Agency: De-centring Charac...mentioning
confidence: 99%
“…However, new issues emerge when teachers' agency is affirmed. While in some of the literature teachers' agency is seen as synonymous with change, either explicitly [5,29] or implicitly [30], it has also been found that teachers can employ their agency to resist change [31]. In the words of Priestley et al [9] (pp.…”
Section: Theoretical Background 21 Professional Agencymentioning
confidence: 99%